I begin of the linking of the education with the social life and the work - Jaqueline Antonella Martínez Gallardo; Enrique Espinoza Freire (Maestro y Sociedad, 2018)
The school to certify its acting should work with educational methodological principles as it is the linking with the social life; the university directive should be qualified in the understanding of the institutions like organization leader in the creation of a sustainable society. The objective of the present work looks for to revise the scientific arguments that define the interaction school community like a social value. The strategy of the study is based on the methodology hermeneutics to arrive to a creative understanding of the scientific texts. The obtained results are centered in modifications to achieve by means of a debate among the family, educational and directive for viabilizar agreements participativos; a sincronía of the school with the context in which the community evolves.